1983
DOI: 10.1901/jaba.1983.16-13
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Analysis in Consumer Affairs: Encouraging Dental Professionals to Provide Consumers With Shielding From Unnecessary X‐ray Exposure

Abstract: An unobtrusive observation system was developed to determine the extent to which dental professionals in two communities provided lead shielding to patients during X-ray exams. A lengthy baseline revealed low and irregular provision of shielding among half of these professionals. Subsequently, a program was undertaken by a consumer's group in which these professionals were requested to provide shielding and were given confidential feedback regarding its use during the baseline period. The provision of shieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…It is undear, in the case of AIDS, whether such assurances could either be extended by health authorities or confidently accepted by patients themselves. Perhaps this concern could be resolved by having patients or their representatives participate substantially in the management ofthe health care system (Greene & Neistat, 1983). If so, such a blending of behavioral and medical technologies with regard for civil liberties may contribute significantly to the development of an effective and socially acceptable system through which the negative impact of STDs and other infectious diseases can be better addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is undear, in the case of AIDS, whether such assurances could either be extended by health authorities or confidently accepted by patients themselves. Perhaps this concern could be resolved by having patients or their representatives participate substantially in the management ofthe health care system (Greene & Neistat, 1983). If so, such a blending of behavioral and medical technologies with regard for civil liberties may contribute significantly to the development of an effective and socially acceptable system through which the negative impact of STDs and other infectious diseases can be better addressed.…”
Section: Discussionmentioning
confidence: 99%
“…A later study demonstrated that the engagement rates of people with dementia in daily activities could be increased by improving nursing assistants' use of prompts and praise (Engelman, Altus, & Mathews, 1999). The use of lead shielding during X-ray exams by dental technicians was increased and maintained for up to nine months through the use of confidential feedback (Greene & Neistat, 1983).…”
Section: Organizationsmentioning
confidence: 99%
“…Numerous papers portray an array of different styles of operant research on consumer behaviour and marketing management. For instance, Rajala and Hantula (2000) describe laboratory experiments with 'consumers'; three contributions in applied behaviour analysis describe field experiments involving consumer behaviour or evaluations and service providers' responses (Crowell et al, 1988;Greene and Neistat, 1983;Greene et al, 1984); three more describe the application of a theoretical model based on behavioural psychology, via survey research, to retail management (Berry, 1968(Berry, , 1969Kunkel and Berry, 1968); and another, the use of a survey to evaluate the behavioural perspective model (Foxall and Greenley, 2000). Interpretive approaches to marketing management in its widest sense have also been undertaken; Rakos (1993) applies behaviour analytic concepts to propaganda; while Foxall (1994Foxall ( , 2001a integrates behaviour analytic research on environmental conservation and marketing mix management, a blueprint perhaps for a more comprehensive integration of the disciplines at the core of consumer behaviour analysis.…”
Section: Operant Research and Marketing Interpretationmentioning
confidence: 99%
“…The marketing of professional services is a dominant theme in current marketing research which concentrates especially on 'the service encounter', the process in which the providers and users of the services in question meet and relate to one another. Greene and Neistat (1983) describe a field experiment in which a consumers' group requested dentists, whose use of lead shielding to protect their patients from X-ray emission had been shown to be deficient, to undertake shielding. The provision of feedback to these professionals resulted in a 'dramatic' increase in shielding which was maintained over a 9-month follow-up period.…”
Section: Foundations Of Consumer Behaviour Analysis Gordon R Foxallmentioning
confidence: 99%